PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KEMAMPUAN BERBAHASA INDONESIA MAHASISWA - Istiqomah; Sekar Loka Pratiwi; Annisa Rohimah; Imalona Tampubolon; Siti Nurul Falah; Zefani Amelia; Rosmaini (STKIP Subang, 2026)
This study aims to analyze the influence of social media usage on students’ Indonesian language skills. The research employed a descriptive quantitative approach involving 20 university students from several study programs at Universitas Negeri Medan. Data were collected through questionnaires distributed via Google Forms covering indicators such as the frequency of slang usage, language use context, interference of slang in formal communication, and students’ perceptions of standard Indonesian usage. The results showed that the use of slang among students was relatively high, reaching 85%. Social media became the main factor influencing the emergence of non-formal language in students’ daily communication. About 65% of students admitted that they often mixed slang with formal Indonesian in academic communication. In addition, 63.2% of respondents realized that excessive slang usage could affect their ability to use proper and correct Indonesian. This study indicates that social media has both positive and negative impacts on students’ language skills. Therefore, students’ awareness and lecturers’ guidance are needed to maintain the proper use of Indonesian in academic environments.